1992
DOI: 10.1530/jrf.0.0960673
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microscopy of the subepithelial capillary plexus of the endometrium of rats during embryo implantation

Abstract: Summary. Using in vivo microscopy we investigated endometrial microvascular events occurring on days 5 and 6 of pregnancy at the time of implantation. Blood flow through the endometrium was visualized using incident-light fluorescence microscopy and a video image was recorded for subsequent analysis. At 17:00 h on day 5 of pregnancy it was not possible to identify the impending implantation site from the in vivo appearance of the subepithelial capillary plexus. At 09:00 h on day 6 of pregnancy the embryo impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A possible role for the high levels of VEGF expression seen at the site of implantation is suggested by recent measurements of capillary diameter at the implantation site in rats (Tawia and Rogers, 1992). These authors showed that large increases in capillary diameter occur in response to local signals associated with the implanting embryo, and suggest that these are associ¬ ated with alterations in the endothelial cells or the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A possible role for the high levels of VEGF expression seen at the site of implantation is suggested by recent measurements of capillary diameter at the implantation site in rats (Tawia and Rogers, 1992). These authors showed that large increases in capillary diameter occur in response to local signals associated with the implanting embryo, and suggest that these are associ¬ ated with alterations in the endothelial cells or the basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may also have been due to the effects of fixation artefact and shrinkage in histology specimens as well as a consequence of studying perfused vessels in live human subjects versus non-perfused vessels in post-mortem eyes (Rastogi et al, 2013). Other plausible explanations for increased capillary diameter in svOCT images may be due to the dynamic effects of physiological variables such as blood pressure, tissue interstitial pressure and vessel wall elasticity acting upon capillary beds (Tawia and Rogers, 1992). These variables have been shown to influence the anatomical dimensions of live tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant impact on future generations, our understanding of the uterine microcirculation in either pregnant (Rogers, 1992; Tawia and Rogers, 1992; Ruttner et al, 2000) or non-pregnant states (Rogers and Macpherson, 1990; Alsip et al, 1996; Hill et al, 1997; Sweeney et al, 1999) remains limited (Osol and Moore, 2014). While isolated microvascular preparations have provided crucial mechanistic data regarding vascular remodeling associated with pregnancy and gestational disease (e.g.…”
Section: Discussionmentioning
confidence: 99%